A Novel Analytical Technique for Optimal Allocation of Capacitors in Radial Distribution Systems - Nawaz, Sarfaraz; Bansal, Ajay Kumar; Sharma, Mahaveer Prasad (Journal of Engineering and Technological Sciences, 2017)
In this paper, a novel analytical technique is proposed to determine the optimal size and location of shunt capacitor units in radial distribution systems. An objective function is formulated to reduce real power loss, to improve thevoltage profile and to increase annual cost savings. A new constant, the Loss Sensitivity Constant (LSC), is proposed here. The value of LSC decides the location and size of candidate buses. The technique is demonstrated on an IEEE-33 bus system at different load levels and the 130-bus distribution system of Jamawa Ramgarh village, Jaipur city. The obtained results are compared with the latest optimization techniques to show the effectiveness and robustness of the proposed technique.